Molecular Profiling of Druggable Targets in Clear Cell Renal Cell Carcinoma Through Targeted RNA Sequencing - van den Heuvel, Corina N. A. M.; van Ewijk, Anne; Zeelen, Carolien; de Bitter, Tessa; Huynen, Martijn; Mulders, Peter; Oosterwijk, Egbert; Leenders, William P. J. (Frontiers in Oncology, 2019)
Clear cell renal cell carcinoma (ccRCC) comprises more than 80% of all renal cancers and when metastasized leads to a 5-year survival rate of only 10%. The high rate of therapy failure and resistance development calls for reliable methods that provide information on the actionable biological pathways and predict optimal treatment protocols for individual patients. We here applied targeted RNA sequencing (t/RNA-NGS) using single molecule Molecular Inversion Probes on tumour nephrectomy samples of five ccRCC patients, comparing tumour with healthy kidney tissues. Transcriptome profiling focused on expression of genes with involvement in ccRCC biology that can be targeted with clinically available drugs. Results confirm high expression of vascular endothelial growth factor-A (VEGF-A) in tumour tissue relative to healthy-appearing kidney, in line with the angiogenic nature of ccRCC. PDGFRα and KIT, targets of the multi-kinase inhibitor sunitinib which is one of the current choices of first-line drug in metastasized ccRCC patients, were expressed at relatively low levels in tumour tissues, whereas significantly increased in normal kidney. Of all measured druggable tyrosine kinases, MET, AXL or EGFR were expressed at higher levels in tumours than in normal kidney tissues, although intertumour differences were observed. Using cancer cell lines we show that t/RNA-NGS gene expression profiles can be used to predict in vitro sensitivity to targeted drugs. In conclusion, t/RNA-NGS analysis may provide insights into the (druggable) molecular make-up of individual renal cancers, and may guide personalized therapy of renal cell cancers.